Hermit crab (Decapoda, Anomura) attraction to dead gastropod baits in an infralittoral algae bank - Pezzuti,Juarez C. B. (2002)
Hermit crabs use gastropod shells as shelter and are adapted to follow chemical cues released from tissues of dead or injured gastropods as a way to find new and more adequate shells. The species composition, crab size, shell types adequacy and physical condition were compared between attracted individuals and crabs collected in previous samples. The previous sampling was carried out in five areas before each experiment. Then, five baits of crushed gastropods in nylon net bags were installed in these areas. Three samples were taken at 30min intervals, capturing all crabs within a circle of 60cm diameter. Attraction of hermit crabs was tested for four different gastropod baits to verify specificity of the chemical cues. Clibanarius antillensis, Pagurus brevidactylus and Paguristes tortugae were collected in the study area. Pagurus brevidactylus, the smallest species, turned out to be more attracted than the 2 other species. The results showed that attracted crabs utilized more gastropod shell types than that collected in previous samples, however shell utilization pattern did not differ between them. Attracted animals were slightly smaller (shield length) than those collected in the previous samples but did not present significant differences in shell adequacy and condition. The four experimental baits attracted the crabs in similar ways not indicating a specific response from the crabs. The fact that attracted animals were smaller suggested that the attraction to dead gastropods might enable the acquisition of a new and larger shell and, consequently, chains of shell exchange between the attracted crabs.